Design Improvement Of Photobioreactor - Lee, Ming Wei (Universiti Sains Malaysia, 2019)
This project aimed to design a new photobioreactor that improve from the current existing photobioreactor. In order to design a new photobioreactor with the improvements, thus studies are required on the parameters that important and affect the cultivation process of the microalgae. This project also applied several techniques and knowledge of product design during the designing process for the photobioreactor. This is very important because the photobioreactor is also considered as a product for the industrial use, therefore the techniques for product design must be applied. The techniques uses are such as data collection of customer needs, concept generation, concept screening, concept selection, failure mode and effect analysis and other knowledges also have been used. The failure mode and effect analysis is important to detect the possible failure occurs in the design and provide the solution for each possible failure. Finally, the new photobioreactor designed and fabricated is able to control and adjust the light intensity, air flow rate and also equipped with filtration system where the design are improved compared to the existing photobioreactor which the filtration system (centrifugation filtration) worked as separate system.